Work place based assessment of medical interns on surgical asepsis following training in Obstetrics and Gynecology - Bangal, Vidyadhar B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Internship programme for medical interns is meant to develop basic skills and to have experience in management of common illnesses and emergencies. Medical interns are often posted to the clinical disciplines, without adequate instructions on surgical asepsis and bio-safety measure. Training need was identified for interns in the subject of surgical asepsis. Methods: Hands on training programme was organized for interns that included common procedures performed by them in wards, operation theatre and labour room complex on day to day basis. A pre and post test was performed to assess the gain in knowledge by interns. Subsequently, interns were supervised by residents, nurses and faculty members in labour room, operation theatre and wards. The observations were documented, and immediate feedback was given to interns. Feedback from interns was obtained at the end of the rotation in Obstetrics and Gynecology. Results: There was significant gain in knowledge by interns following training programme. Interns adopted good aseptic precautions during their posting. Compliance to aseptic precautions was significantly more in female interns as compared to male. A demand got generated from other batches of interns in conducting similar training programme for them. Nurses, faculty members and co-ordinator of internship programme gave positive feedback about the changes observed in the batch of interns who underwent training as compared to previous batches. Conclusions: Adoption of techniques of surgical asepsis by interns was improved following training programme held at the beginning of rotation posting in Obstetrics and Gynecology. It is recommended to include the topic in internship orientation programme.